2019
DOI: 10.1103/physrevlett.123.073002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Scalar and Vector Polarizabilities of the Cesium 6sS21/2

Abstract: Using recent high-precision measurements of electric dipole matrix elements of atomic cesium, we make an improved determination of the scalar (α) and vector (β) polarizabilities of the cesium 6s 2 S 1/2 → 7s 2 S 1/2 transition calculated through a sum-over-states method. We report values of α = −268.82 (30) a 3 0 and β = 27.139 (42) a 3 0 with the highest precision to date. We find a discrepancy between our value of β and the past preferred value, resulting in a significant shift in the value of the weak charg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 58 publications
2
18
0
1
Order By: Relevance
“…Another change affected the extraction from the APV measurement in 133 Cs [15], for which the Stark vector transition polarizability needs to be known. The latter has been re-measured [21] very recently, shifting |Q W ( 133 Cs)| which was 1.4 σ lower than what was expected from the SM much closer to the prediction (see the lower part of Figure 1).…”
Section: Introductionsupporting
confidence: 69%
“…Another change affected the extraction from the APV measurement in 133 Cs [15], for which the Stark vector transition polarizability needs to be known. The latter has been re-measured [21] very recently, shifting |Q W ( 133 Cs)| which was 1.4 σ lower than what was expected from the SM much closer to the prediction (see the lower part of Figure 1).…”
Section: Introductionsupporting
confidence: 69%
“…Experimentally, the ratio of the PV amplitude over the Stark vector transition polarizability β is measured (with the most precise results currently available for 133 Cs [112,113]), which then needs to be combined with atomic-theory calculations and independent input for β. The latter can be determined semi-empirically either via a measurement together with another hyperfine amplitude [114,115] or the scalar polarizability [116][117][118], leading to the recommendation β = 27.064 (25) exp (21) th a 3 B [88] in units of the Bohr radius a B , but the uncertainty of this average does not include an error inflation to account for the 2.7σ tension between the two methods. Similarly, the coefficient of the atomic structure calculation has been under debate in the literature [119][120][121][122][123][124], with ref.…”
Section: Atomic Parity Violationmentioning
confidence: 99%
“…We note that the authors of [10] have recently reported using new precision data and an alternate technique to determine the vector polarizability β needed to extract the (APV) weak charge of cesium. Their result differs from the currently accepted value of β, which shifts the extracted weak charge of cesium (and thus the corresponding sin 2̂) closer to the SM value than shown in Figure 4.…”
Section: The Weak Mixing Angle Sin 2 θWmentioning
confidence: 99%